2019
DOI: 10.1002/adfm.201904403
|View full text |Cite
|
Sign up to set email alerts
|

Membrane‐Free Detection of Metal Cations with an Organic Electrochemical Transistor

Abstract: Alkali-metal ions are the messengers of all living cells, governing a cascade of physiological processes through the action of ion channels. Sodium (Na +) and potassium (K +) are the two alkali metals found in human blood serum. Devices that can monitor, in real time, the concentrations of these cations in aqueous media are in demand not only for the study of cellular machinery and dysfunctions, but also to detect conditions in the human body that lead to electrolyte imbalance, such as hypernatremia, hyperkale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
104
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(113 citation statements)
references
References 48 publications
1
104
0
1
Order By: Relevance
“…The OECT is an electrolyte gated transistor consisting of a (semi)conducting polymer film deposited between two metal electrodes (the source and the drain), and a gate electrode that is physically separated from the channel through an electrolyte . Because of the high gain of these devices resulting from the volumetric charging of the CP channel upon application of a gate voltage, the OECT configuration has been explored to sense a variety of biologically relevant species such as metabolites, ions, neurotransmitters and proteins such as Immunoglobulin G and amyloid beta . Ever since this first report of the electrodeposited OECT channel, only a recent work has demonstrated that a CP can be electropolymerized within the source and drain electrodes separated by a few tens of micrometers .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The OECT is an electrolyte gated transistor consisting of a (semi)conducting polymer film deposited between two metal electrodes (the source and the drain), and a gate electrode that is physically separated from the channel through an electrolyte . Because of the high gain of these devices resulting from the volumetric charging of the CP channel upon application of a gate voltage, the OECT configuration has been explored to sense a variety of biologically relevant species such as metabolites, ions, neurotransmitters and proteins such as Immunoglobulin G and amyloid beta . Ever since this first report of the electrodeposited OECT channel, only a recent work has demonstrated that a CP can be electropolymerized within the source and drain electrodes separated by a few tens of micrometers .…”
Section: Methodsmentioning
confidence: 99%
“…The PEDOT film exhibits a relatively smooth surface, while EDOTOH‐based film surfaces are rougher with a larger area, which is expected to contribute to the high capacitance (compare Figure c with d and e). The dense population of OH groups in the homopolymer pEDOTOH, however, may lead to steric hindrance during bioconjugation, providing a low degree of conformational freedom for biorecognition units . Second, EDOTOH monomer has low solubility in water with aggregates visible to bare eye in the reaction mixture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two types of crown-ether functionalized EDOT monomers were synthesized and electropolymerized on the microscale gate electrodes of OECTs ( Figure 8B, i). [144] The ring-size of the crownether unit determines which cation, sodium (Na + ) or potassium (K + ), will be captured in the measurement solution. Each metal cation that complexes with a corresponding crown ether unit in the bulk of the porous conducting polymer film electrochemically reduces the film at the gate electrode ( Figure 8B, ii).…”
Section: Chemically Functionalized Cps For Biosensingmentioning
confidence: 99%
“…Reproduced with permission. [144] Copyright 2019, Wiley-VCH. C-i) An NDI-T2-based copolymer, P-90, has electrical contact with glucose oxidase drop cast on top of its film.…”
Section: Chemically Functionalized Cps For Biosensingmentioning
confidence: 99%